Efficacy of gelatamp in controlling the postoperative sequelae following mandibular posterior teeth extraction - A split-mouth study - Mathew Joseph Thuruthel; L.K. Surej Kumar; Nikhil M. Kurien; Mathew Tharakan (Journal of Oral Biology and Craniofacial Research)
Purpose: This study aimed to evaluate the effectiveness of gelatamp on soft tissue healing, bleeding, and pain following mandibular posterior teeth extraction. Methods: This study was designed as a split-mouth, prospective randomized double-blind controlled trial conducted in a single tertiary care center. Thirty-five subjects indicated for routine mandibular posterior teeth extraction were divided into two groups using the lottery technique: the experimental group (n = 30), which received gelatamp after extraction, and the control group (n = 30), which received no intervention. The primary outcomes included soft tissue healing(Landry, Turnbull, Howley index) and Pain(VAS score). The secondary outcomes assessed were bleeding(Maani et al. index) and swelling(Sauza and Consone assessment). Result: The results showed a statistically significant difference in soft tissue healing on the third and seventh days in the experimental group (p ≤ 0.05) than in the control group. A significant difference in bleeding scores at 5 min, 30 min, and 2 h postoperatively in the study group (p ≤ 0.05) was noted. There was no significant difference between the groups for pain on the first, third or seventh day postoperatively (p ≤ 0.05). The swelling assessment also showed no significant changes (p = 0.831) for the study and the control group. Conclusion: Based on the findings of this study, gelatamp can be effectively used to reduce postoperative sequelae such as bleeding with better soft tissue healing following extractions and surgical removal of tooth.